ANALISIS FAKTOR SANITASI KAPAL TERHADAP TANDA─TANDA KEBERADAAN TIKUS (Studi pada Kapal Penumpang yang Bersandar di Pelabuhan Kalianget 2019) - Nanda Aprillia Mifthakul Ni'ma; Suprijandani .; Ngadino . (GEMA LINGKUNGAN KESEHATAN, 2020)
Ship sanitation is one of the efforts shown on environmental risk factors in shipbuilding to decide the chain of disease transmission to maintain and enhance health status. This research was conducted to see the relationship between ship sanitation and signs of existence of mice on passenger ships that lean in Kalianget Port in 2019This type of research is descriptive by using a cross sectional approach. The sample in the research was in the form of 4 passenger ships. Data collection through  assessment with forms. Vessel sanitation assessment uses a pH meter, Luxmeter, and Hygrometer tool. The instrument used is a vessel sanitation inspection form and examination of signs of the presence of mice on board. The results of this study indicate that ship sanitation with signs of the presence of mice on board a passenger who has no connectionBased on the obstacles faced during the collection of vessel sanitation data and signs of the presence of rats because of the weather during the rainy season so that many ships are not operating. Suggestions that can be given from this study include the existence of research on ship sanitation implementation on signs of the presence of rats on passenger ships that lean. Keywords: Ship Sanitation, Signs of Rat Existence